Material studies for the recycling of abandoned, lost or otherwise discarded fishing gear (ALDFG). Issue 7 (July 2022) - Weißbach, Gunter; Gerke, Gilian; Stolte, Andrea; Schneider, Falk
This study investigates the feasibility of material recycling for retrieved gillnets from the Baltic Sea collected during a campaign of the World Wildlife Fund (WWF) Germany. Fragments from the material were analysed by Fourier transform infrared (FTIR) spectroscopy revealing polyamide 6 (PA6), polypropylene (PP) and polyethylene terephthalate (PET) in net material, swim lines and sink lines, respectively. A visual examination by microscope found large quantities of minerals attached to the surface of the material as well as in knots and loops of the polymer structure. Ash tests showed that a pre-treatment of the material including sorting, shredding, density separation and washing allows to reduce the mineral content from more than 45% of the total to 1.1%. However, for a separation by density, it is important that the entangled fibres can move freely. This is a major challenge for a primary or secondary mechanical recycling because a substantial fibre length reduction is required for the small polymer fibres down to a diameter of 20 µm. Another challenge for all kinds of recycling is the presence of lead lines in gillnets. Automated technology for removing these does not exist until now. A manual removal is indispensable to limit the level of contamination. Due to the complex pre-treatment and the elevated heavy metal concentrations also a tertiary or feedstock recycling seems not to be a possible pathway for retrieved gillnets. Yet, other options such as a primary recycling in concrete or bitumen additives or quaternary recycling via incineration may be conceivable alternatives. But there are also some arguments against these options. Better product design must be the goal to prevent plastic pollution and establish a functioning circular economy. In this context, the heavy metal contamination by abandoned, lost or otherwise discarded fishing gear (ALDFG) must be stopped.